Peran Kecerdasan Spiritual dalam Memaknai Kebahagiaan Mahasiswa di Era Digital: Perspektif Psikologi Islam - Annisa Oktaviani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
This study examines the role of spiritual intelligence in shaping students’ understanding of happiness in the digital era from an Islamic psychology perspective. Employing a qualitative phenomenological approach, the research involves university students who actively engage with social media. Data were collected through in-depth interviews, observations, and documentation, and analyzed using thematic analysis. The findings reveal a significant shift in the meaning of happiness, from a substantive and intrinsic concept to a more symbolic and externally driven construct influenced by digital culture and online validation. Nevertheless, spiritual intelligence functions as a reflective and stabilizing mechanism, enabling students to reinterpret happiness as a deeper, more meaningful inner state. From the perspective of Islamic psychology, true happiness (sa’adah) is grounded in closeness to God and the internalization of spiritual values in daily life. This study underscores the importance of spiritual intelligence in addressing psychological challenges in the digital age and fostering a more balanced and authentic sense of well-being among students.